Evaluation of cardiac involvement in patients with clinical post-COVID-19 syndrome. (3rd October 2022) - Gorecka, M; Jex, N; Thirunavukarasu, S; Chowdhary, A; Poenar, A M; Sharrack, N; Swoboda, P P; Xue, H; Vassiliou, V; Kellman, P; Plein, S; Simms, A; et al.
Abstract: Introduction: The underlying pathophysiology of Post-COVID-19 syndrome remains unknown, but increased cardiometabolic demand and state of mitochondrial dysfunction have emerged as candidate mechanisms. Cardiovascular magnetic resonance (CMR) provides insight into pathophysiological mechanisms underlying cardiovascular disease and 31-phosphorus magnetic resonance spectroscopy (31P-MRS) allows non-invasive assessment of the myocardial energetic state. Purpose: We sought to assess whether Post-COVID-19 syndrome is associated with abnormalities of myocardial structure, function, perfusion and tissue characteristics or energetic derangement. Methods: Prospective case-control study. A total of 20 patients with a clinical diagnosis of Post-COVID-19 syndrome (seropositive) and no prior underlying cardiovascular disease (CVD) and ten matching controls underwent 31P-MRS and CMR at 3T at a single time point. (Figure 1) All patients had been symptomatic with acute COVID-19, but none required hospital admission. Results: Between the Post-COVID-19 syndrome patients and matched contemporary controls there were no differences in myocardial energetics (phosphocreatine to ATP ratio), in cardiac structure (biventricular volumes, left ventricular mass), function (biventricular ejection fractions, global longitudinal strain), tissue characterization (T1 and extracellular volume [ECV] fraction mapping, late gadolinium enhancement) or perfusion (myocardial rest and stress blood flow, myocardial perfusion reserve). One patient with Post-COVID-19 syndrome showed subepicardial hyperenhancement on the late gadolinium enhancement imaging compatible with prior myocarditis, but no accompanying abnormality in cardiac size, function, perfusion, ECV, T1, T2 mapping or energetics. This patient was excluded from statistical analyses. (Table 1) Conclusion: In this study, the overwhelming majority of patients with a clinical Post-COVID-19 syndrome with no prior CVD did not exhibit any abnormalities in myocardial energetics, structure, function, blood flow or tissue characteristics. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Welcome Trust Clinical Career Development Fellowship (221690/Z/20/Z);NIHR-UKRI COVID-19 Rapid Response Rolling Call (COV0254)ESC Training Grant